Encapsulated Perovskites: Self‐Structural Healing of Encapsulated Perovskite Microcrystals for Improved Optical and Thermal Stability (Adv. Mater. 21/2021). Issue 21 (26th May 2021) - Li, Ruxue; Li, Bobo; Fang, Xuan; Wang, Dengkui; Shi, Yueqing; Liu, Xiu; Chen, Rui; Wei, Zhipeng
Abstract : A self‐sufficient micrometer‐level vacuum growth chamber based on encapsulated MAPbBr3 microcrystals is designed by Rui Chen, Zhipeng Wei, and co‐workers, as described in article number 2100466 . Perovskite materials with enhanced environmental, thermal, and optical stability through the reduction of deep‐level trap states due to self‐structural healing are observed. This greatly improves the lasing performance and service cycle.